TRANSFORMATION OF ENGLISH AND UZBEK COMPUTER AND INTERNET VOCABULARY IN ONLINE MEDIA (International journal of artificial intelligence, 2025)
This article explores the dynamic transformation of English and Uzbek computer and internet vocabulary within online media environments. With the rapid expansion of digital technologies and globalization of communication, English has become a dominant source of technical and digital terminology worldwide. The Uzbek language, like many others, has been absorbing English-origin terms, especially through online platforms such as social media, news websites, and blogs. This paper analyzes how such vocabulary is adapted, borrowed, hybridized, or semantically expanded in Uzbek digital discourse, highlighting linguistic, sociocultural, and stylistic implications of this transformation.